EFEKTIVITAS PEMBERIAN AIR LERI TERHADAP PERTUMBUHAN DAN HASIL JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Ummu Kalsum; Siti Fatimah; Catur Wasonowati (Agrovigor, 2011)
White oyster mushroom is kind of consumed mushroom that has delicious taste and efficacious drug. Mushroom need nutrition addition to increase growth and development so that better production, like nutrition from rice washing water. The contain are carbon element, nitrogen, mineral and vitamin B. This experiment aim to determine addition of rice washing water effect, optimal volume and time interval on growth and yield of white oyster mushroom (Pleurotus ostreatus). This experiment is carried out at mushroom’s house Maduraya Agro Kamal. The research design used was factorial completely randomized design with two factors. First factor is addition rice washing water volume with 4 level, that is without addition rice washing water (A0), addition rice washing water as much as 20 ml/1000 g substrat (A1), 40 ml/1000 g substrat (A2) and 60 ml/1000 g substrat (A3). Second factor is addition time interval that consists of 2 level, that is 2 days (B1) and 4 days (B2). Experiment result shows that interaction between volume treatment and addition time interval give effect on fruit body total. Addition rice washing water volume treatment give real effect on maximal pileus fruit width. While addition time interval treatment does not give significant difference on all parameters but it can increase pileus fruit width, total weight and biological efficiency. Interaction of volume treatment and addition time interval is the best combination is volume treatment 40 ml/1000 g substrat with time interval 2 days (A2B1), this matter is showed in lot fruit body total as big as 8,871 fruit. Addition rice washing water volume 40 ml/1000 g substrat is the best volume that indicated from first bud appear, first harvest time, total weight and biological efficiency.